The ultra-precision Ud-lap grinding of flat advanced ceramics - Fiocchi, Arthur Alves; De Angelo Sanchez, Luiz Eduardo [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Fortulan, Carlos Alberto (Elsevier, 2016)
The present study focuses on the Ud-lap grinding process and its machine-tool design aiming at ultra-precision (UP) manufacturing of advanced ceramics. Impacts of three different overlapping factors on a dressing (Ud) and three abrasive grit sizes of conventional SiC grinding wheels were analyzed on flat nanometric surface finishing of dense discs of 3Y-TZP in a ductile regime of material removal. Microhardness, contact and optical profilometry, SEM-FEG, Raman spectroscopy, XRD, and confocal epi-fluorescence were applied to characterize the ceramic material. Mechanical and electric-electronic designs of the machine-tool were developed toward the UP ceramic grinding. The design methodology was successful for supporting the achievement of all design requirements of the CNC Fiocchi Lap Grinder. The machine-tool and the Ud-lap grinding process were capable of manufacturing flat 3Y-TZP surfaces with nanometric finishing without introducing critical defects. The best finishing, Ra = 60.63 nm, came from the #300 grinding wheel dressed with Ud = 5. A flatness deviation of 0.308 μm was obtained through the #800 grinding wheel and Ud = 3. Differences between theoretical and real macro and micro effects over the grinding wheels after single-point diamond dressing, epoxy bond strength, abrasive protrusion, abrasive grit size and abrasive friability play a key role in the Ud-lap grinding. There is no report of an abrasive process capable of achieving similar nanometric finishing without introducing critical defects with the same micrometric grit size and type of abrasive. The Ud-lap grinding can replace the engagement of processes such as grinding, lapping, and polishing of advanced ceramics.
Keywords: Advanced ceramics; Ductile grinding; Nanotechnology; Surface characterization; Ud-lap grinding